Pengaruh Pengetahuan Akuntansi dan Motivasi Kerja Terhadap Manfaat Penggunaan Informasi Akuntansi pada Pelaku UMKM di Kecamatan Lowokwaru - Riska Dewi Safitri; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2023)
This study aims to examine and analyze the influence of accounting knowledge and work motivation on the benefits of using accounting information for UMKM actors in Lowokwaru sub-district. This research is a quantitative research. In this study, data were collected from questionnaires distributed to 84 respondents using a purposive sampling technique with the criteria of UMKM respondents engaged in the fashion sector. The analysis used includes instrument trials (validity and reliability tests), prerequisite tests (normality tests and linearity tests), classical assumption tests (multicollinearity tests and heteroscedasticity tests), multiple linear regression analysis, and hypothesis testing (F statistical tests, determination tests R2 , statistical test t). The results of this study obtained: 1) accounting knowledge and work motivation simultaneously have a positive and significant effect on the benefits of using accounting information. 2) accounting knowledge has a positive and significant effect on the benefits of using accounting information on UMKM actors. 3) work motivation has a positive and significant effect on the benefits of using accounting information on UMKM actors.Keywords: Knowledge of accounting, work motivation, use of accounting information